Enhancing Earthquake Disaster Identification Through Probabilistic Seismic Hazard Analysis and Expert Systems - Felix Hayden; Eric Eugene (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2023)
This research endeavors to revolutionize earthquake disaster identification and mitigation through the creation of an advanced expert system grounded in Probabilistic Seismic Hazard Analysis (PSHA) methodologies. Leveraging a comprehensive amalgamation of sophisticated algorithms, seismic data, and expert knowledge, this study aims to enhance the precision, accuracy, and timeliness of seismic hazard assessments. The research commences with an in-depth exploration of earthquake disasters, highlighting their profound societal impact, infrastructural vulnerabilities, and the imperative for proactive disaster management strategies. The introduction of the expert system forms the crux of this research, delineating its architecture, key components, and the integration of PSHA methodologies. This system harnesses seismicity rate models, fault rupture models, ground motion prediction models, and probabilistic combination models within a cohesive framework, facilitating comprehensive seismic hazard assessments. The research outlines the primary objective: to design and develop an expert system that harnesses PSHA to identify potential earthquake disasters with heightened accuracy and reliability. The methodology section details the algorithms, models, and computational techniques employed within the expert system, elucidating their collective role in estimating seismic hazard probabilities. The outcomes of this research encompass identified potential earthquake disaster scenarios, characterized by seismic hazard probabilities, ground shaking intensities, and vulnerability assessments. These findings offer actionable insights for policymakers, urban planners, emergency responders, and communities, fostering informed decision-making and resilience-building initiatives.